Implementation of Learning During the Covid 19 Pandemic for Class 1 SD/MI - Rizal, Setria Utama; Mazrur, Mazrur; Syabrina, Muhammad; Hikmah, Nurul; Mualimin, Mualimin (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to identify the learning methods employed during the COVID-19 pandemic for first-grade students in SD/MI schools in Palangka Raya City. Utilizing a descriptive qualitative approach, data were collected through interviews, observations, and documentation from school principals and first-grade teachers at four different SD/MI schools. The study employed Miles and Huberman's data analysis techniques, incorporating triangulation for data validation. The findings reveal four distinct learning methods implemented during the pandemic: online learning, limited face-to-face learning (PTMT), health protocol-compliant face-to-face learning, and complete offline face-to-face learning. Online learning was primarily used when strict social distancing measures were in place. PTMT was adopted to combine online and limited in-person sessions, ensuring minimal physical interaction. Health protocol-compliant face-to-face learning involved strict adherence to health guidelines during in-person classes. In contrast, complete health protocol offline face-to-face learning resumed normal classroom activities when permitted. The research concludes that these methods varied in effectiveness and adaptation based on the schools' resources and students' needs. This study highlights the diverse approaches schools took to maintain educational continuity, showcasing the flexibility and resilience of the education system in Palangka Raya City during the pandemic.